2012
DOI: 10.1038/cdd.2012.150
|View full text |Cite
|
Sign up to set email alerts
|

Type-3 metabotropic glutamate receptors regulate chemoresistance in glioma stem cells, and their levels are inversely related to survival in patients with malignant gliomas

Abstract: Drug treatment of malignant gliomas is limited by the intrinsic resistance of glioma stem cells (GSCs) to chemotherapy. GSCs isolated from human glioblastoma multiforme (GBM) expressed metabotropic glutamate receptors (mGlu3 receptors). The DNAalkylating agent, temozolomide, killed GSCs only if mGlu3 receptors were knocked down or pharmacologically inhibited. In contrast, mGlu3 receptor blockade did not affect the action of paclitaxel, etoposide, cis-platinum, and irinotecan. mGlu3 receptor blockade enabled te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 47 publications
1
61
1
Order By: Relevance
“…Possibly, TMZ reduces the intrinsic epileptogenicity of the tumour through a decrease in glutamate levels released from glioma cells 11. Furthermore, a downregulation of glutamate receptors is associated with a reduction in the risk of seizures as well as with increased survival in glioma patients treated with adjuvant TMZ 38. Changes in the peritumoural microenvironment might also be induced, for example, through an inhibition of the immune response or restoring the neurotransmitter synthesis 39 40…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, TMZ reduces the intrinsic epileptogenicity of the tumour through a decrease in glutamate levels released from glioma cells 11. Furthermore, a downregulation of glutamate receptors is associated with a reduction in the risk of seizures as well as with increased survival in glioma patients treated with adjuvant TMZ 38. Changes in the peritumoural microenvironment might also be induced, for example, through an inhibition of the immune response or restoring the neurotransmitter synthesis 39 40…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mGluR3 inhibition eliminated this constraint and promoted astroglial differentiation [68, 73, 76, 78]. (6) Accordingly to Arcella et al (2005) [73] and Ciceroni et al (2013) [77], MAPK axis supported mGluR3-induced GBM proliferation, (7) since mGluR3 stimulation increased Erk1/2 phosphorylation and its blockade reduced p-Erk1/2 levels. mGluR3 inhibition plus MEK1/2 blockade showed an additive antiproliferative effect on GBM cells [68].…”
Section: Glutamate As a Growth Factor For Glioblastomamentioning
confidence: 99%
“…In this context, Ciceroni et al (2013) showed mGluR3 inhibition enables cytotoxic action of TMZ in GSC cultures [77]. TMZ (250 μM) did not affect cell viability when applied alone, but became toxic when combined with LY 341495 (100 nM) and LY 2389575 (100 nM), two mGluR3 antagonists.…”
Section: In Vitro Studies Evaluating the Role Of Mglur On Glioma Prolmentioning
confidence: 99%
“…22,23 Compound 1 has also been used as a tool to establish a potential utility for mGlu 2/3 inhibition in the treatment of glioma. 2427 …”
Section: Introductionmentioning
confidence: 99%